Recycle bin: waste business platform to improve scavenger’s children education based on mobile application / Regita Nurina Salsabila ... [et al.] - Salsabila, Regita Nurina; Arsyad, Ikhwan Shafa; Nurtiara, Sherina Friskila; Fadlilah, Alfa (Universiti Teknologi MARA, Kedah, 2019)
Recycle Bin is business that is engaged in services, kind of technosociopreneur and welfare. Recycle Bin is a platform that focuses on trash services. The services offered are connecting between clients (owners of waste) and waste processors by selling or donating plastic waste online at Recycle Bin as its flagship feature. Not only that, Recycle Bin has several other excellent features, such as beFund, Integrated Scholarship, OrderLung, Green Action Community, T-Shop, and T-News. Recycle Bin has the aim to prosper the education of scavenger’s children by providing education insurance for Indonesian scavenger’s children, the insurance is obtained from the results of transactions carried out by both scavengers and users, with a percentage of 5% per transaction. Recycle Bin is the first platform that breakthroughs in the environmental field by utilizing information technology, which has a goal to prosper the education level of scavenger children in Indonesia. With using Recycle Bin application you have saved 1 scavenger’s child and Indonesia from ignorance. Secondly, the sales system that we use is that we get money from every sale to the Micro, small and medium enterprises who have collaborated with Recycle Bin, and also get from users’ transactions. Thirdly, the uniqueness of the additional features of Recycle Bin's development is that we have a feature to connect our partner and a feature of becoming a waste volunteer, also a feature to CSR, Market, Scholarship Awardee, and news. With Malang as one of city which pay a lot of attention in waste problem, we believe It will be the best solution in welfare.